Ceramic susceptor and manufacturing method for electrostatic chuck
Patent Information
- Application Number
- JP2023128701
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0007】 Moを主成分として含み、且つ、希土類酸化物を添加した金属材料によって電極を形成した場合には、希土類酸化物を添加していないMoを用いた場合と比べて、セラミックスと同時焼成した後におけるMoの粒子径を小さくすることができる。この場合には、同時焼成時の高温下でMoに粒界滑りが生じて塑性変形するため、電極とセラミックスの絶縁層との間に働く応力が緩和される。これにより、セラミックスサセプタの絶縁性能を向上させることができる。また、金属製の電極をセラミックス基材の上面から上下方向に0.3mm以上離れた位置に埋設することにより、電極と半導体ウェハ(基板)間に働く電界強度を一定以下に抑制することができ、セラミックスサセプタの絶縁性能を向上させることができる。
Smart Images

Figure 2025024529000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a ceramic susceptor and an electrostatic chuck. [Background technology]
[0002] Conventionally, a ceramic susceptor has been known in which an electrode (high-frequency electrode or electrostatic attraction electrode) made of a heat-resistant metal (such as W, Mo, or an alloy thereof) of a specified size is embedded in a ceramic sintered body (ceramic base material) such as AlN ceramics (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-77995 A Summary of the Invention [Problem to be solved by the invention]
[0004] The electrodes need to be embedded shallowly from the top surface of the ceramic substrate, and stress can be induced between the electrodes and the insulating layer (the ceramic layer between the top surface of the ceramic substrate and the electrodes) due to differences in shrinkage rate and CTE during firing between the ceramic substrate and the electrodes. This causes variations in the insulation resistance of the ceramic susceptor.
[0005] The present invention has been made in view of the above circumstances, and has an object to provide a technique for improving the insulating performance of ceramic susceptors compared to conventional techniques. [Means for solving the problem]
[0006] According to an aspect of the present invention, there is provided a ceramic substrate having an upper surface and a lower surface facing the upper surface in a vertical direction; A metal electrode is embedded in the ceramic base at a position 0.3 mm or more away from the upper surface in the vertical direction, The electrode is provided with a ceramic susceptor characterized in that it contains Mo as a main component and also contains a rare earth oxide. Effect of the Invention
[0007] When an electrode is formed from a metal material containing Mo as a main component and containing rare earth oxides, the particle size of Mo after co-firing with ceramics can be made smaller than when Mo without rare earth oxides is used. In this case, grain boundary sliding occurs in Mo at high temperatures during co-firing, causing plastic deformation, and the stress acting between the electrode and the insulating layer of the ceramics is alleviated. This can improve the insulating performance of the ceramic susceptor. In addition, by embedding a metal electrode at a position 0.3 mm or more away from the upper surface of the ceramic base material in the vertical direction, the electric field strength acting between the electrode and the semiconductor wafer (substrate) can be suppressed to a certain level or less, and the insulating performance of the ceramic susceptor can be improved. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view of a ceramic susceptor 100. As shown in FIG. [Diagram 2] FIG. 2 is a schematic explanatory diagram of the ceramic susceptor 100. As shown in FIG. [Diagram 3] 1A is a schematic explanatory diagram showing the shape of a high-frequency electrode 124, and FIG. 1B is a schematic explanatory diagram showing the shape of an electrostatic attraction electrode 126. FIG. [Figure 4] FIG. 4 is a schematic explanatory diagram showing the shape of the heater electrode 122. As shown in FIG. [Diagram 5] 1(a) to 1(e) are diagrams showing a flow of a method for producing the ceramic base 110. FIG. [Figure 6] 1(a) to 1(d) are diagrams showing the flow of another method for producing the ceramic base 110. FIG. [Figure 7] FIG. 7 is a table summarizing the results of Examples 1 to 3. [Figure 8] FIG. 8 is a table summarizing the results of Examples 4 to 6. [Figure 9] FIG. 9 is a table summarizing the results of Examples 7 to 9. [Figure 10] FIG. 10 is a table summarizing the results of Comparative Examples 1 and 2. [Figure 11] FIG. 11 is an explanatory diagram showing a state in which fraying occurs in the electrode 120. As shown in FIG. [Figure 12] FIG. 1(a) is an explanatory diagram for explaining burrs protruding above the upper surface of the high-frequency electrode 124, and FIG. 1(b) is an explanatory diagram for explaining a state in which no burrs protruding above the upper surface of the high-frequency electrode 124 remain when multiple through holes 128 in the high-frequency electrode 124 are formed by etching. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Ceramic susceptor 100> A ceramic susceptor 100 according to an embodiment of the present invention will be described with reference to Figs. 1 and 2. The ceramic susceptor 100 according to this embodiment is a substrate holding member for adsorbing and holding a semiconductor wafer such as a silicon wafer (hereinafter simply referred to as a wafer 10). In the following description, the up-down direction 5 is defined based on a state in which the ceramic susceptor 100 is installed so as to be usable (the state in Fig. 1). As shown in Fig. 1, the ceramic susceptor 100 according to this embodiment includes a ceramic base material 110, a heater electrode 122 and a high-frequency electrode 124 (see Fig. 2), a shaft 130, and power supply lines 140 and 141 (see Fig. 2).
[0010] The ceramic base 110 is a member having a circular plate shape with a diameter of 12 inches (about 300 mm), and the wafer 10 to be held is placed on its upper surface 111. In FIG. 1, the wafer 10 and the ceramic base 110 are shown separated from each other to make the drawing easier to see. As shown in FIG. 1, an annular convex portion 152 (hereinafter simply referred to as the annular convex portion 152) and a plurality of convex portions 156 are provided on the upper surface 111 of the ceramic base 110. In FIG. 1, the number of the plurality of convex portions 156 is reduced compared to FIG. 2 to make the drawing easier to see. As shown in FIG. 2, a first gas flow passage 164, which will be described later, is formed inside the ceramic base 110. The ceramic base 110 can be formed of a ceramic sintered body such as aluminum nitride, silicon carbide, alumina, silicon nitride, or the like.
[0011] As shown in FIGS. 1 and 2, the annular protrusion 152 is an annular protrusion disposed on the outer periphery (outer edge) of the upper surface 111 of the ceramic base 110, and protrudes upward from the upper surface 111. As shown in FIG. 2, when the wafer 10 is placed on the ceramic base 110, the upper surface 152a of the annular protrusion 152 abuts against the lower surface of the wafer 10. That is, when the wafer 10 is placed on the ceramic base 110, the annular protrusion 152 is disposed at a position overlapping with the wafer 10 in the up-down direction 5. A plurality of protrusions 156 are provided on the upper surface 111 of the ceramic base 110 inside the annular protrusion 152. All of the plurality of protrusions 156 have a cylindrical shape. That is, the shape of the upper surface 156a of the plurality of protrusions 156 is circular. 2, in order to simplify the drawing, one of the multiple protrusions 156 is illustrated as being disposed approximately at the center of the upper surface 111, and the remaining protrusions 156 are illustrated as being arranged on the circumference of four equally spaced concentric circles. However, the position, shape, and / or number of the protrusions 156 are appropriately set depending on the application, action, and function.
[0012] The height of the annular convex portion 152 can be in the range of 5 μm to 50 μm. Similarly, the height of the plurality of convex portions 156 can be in the range of 5 μm to 50 μm. In this specification, the height of the annular convex portion 152 and the height of the plurality of convex portions 156 are defined as the length in the vertical direction from the upper surface 111 of the ceramic substrate 110. In addition, when the upper surface 111 of the ceramic substrate 110 is not flat and has, for example, a step, the highest position of the upper surface 111 of the ceramic substrate 110 is used as a reference and the height is defined as the length in the vertical direction from that point.
[0013] 2, an opening 164a of a first gas flow passage 164 is formed on the upper surface 111 between the innermost concentric circle in which the multiple protrusions 156 are arranged and the second innermost concentric circle. The first gas flow passage 164 is a gas flow passage having the opening 164a, and is formed inside the ceramic base material 110. The first gas flow passage 164 extends downward from the opening 164a. As described later, a lower end of the first gas flow passage 164 is joined to an upper end of a second gas flow passage 168 formed inside the shaft 130.
[0014] The first gas flow passage 164 can be used as a flow passage for supplying gas to a space (gap) defined by the upper surface 111 of the ceramic base 110 and the lower surface of the wafer 10. For example, a heat transfer gas for heat transfer between the wafer 10 and the ceramic base 110 can be supplied. For example, an inert gas such as helium or argon, or nitrogen gas can be used as the heat transfer gas. The heat transfer gas is supplied through the first gas flow passage 164 at a pressure set within a range of 100 Pa to 40000 Pa. In addition, when the process gas invades the gap inside the annular protrusion 152 from the gap between the upper surface 152a of the annular protrusion 152 and the lower surface of the wafer 10, the gas can be exhausted through the first gas flow passage 164. At this time, the differential pressure between the pressure outside the gap and the pressure inside the gap can be adjusted by adjusting the exhaust pressure. As a result, the wafer 10 can be adsorbed toward the upper surface of the ceramic base 110.
[0015] 2, a heater electrode 122 and a high-frequency electrode 124 are embedded inside the ceramic base 110. The high-frequency electrode 124 is embedded above the heater electrode 122. The high-frequency electrode 124 can be embedded at a position 0.3 mm to 2.0 mm below the upper surface 111 of the ceramic base 110. In other words, the thickness D of the ceramic insulating layer from the upper surface 111 of the ceramic base 110 to the high-frequency electrode 124 can be 0.3 mm or more and 2.0 mm or less.
[0016] 3(a), the high-frequency electrode 124 has a circular shape. The outer diameter of the high-frequency electrode 124 can be, for example, 298 mm. By applying a predetermined high-frequency voltage to the high-frequency electrode 124, plasma can be generated above the ceramic base 110.
[0017] The high-frequency electrode 124 can be formed of a mesh, foil, or plate material made of woven wires of a metal material containing molybdenum (Mo) as a main component and having rare earth oxide added thereto (hereinafter referred to as rare earth-added Mo). In this specification, containing Mo as a main component means that the Mo content is 50% or more. For example, La2O3 and CeO2 can be used as rare earth oxides. The foil is a metal material having a thickness of less than 0.1 mm, and the plate is a metal material having a thickness of 0.1 mm or more. When the high-frequency electrode 124 is formed of a foil or plate material of rare earth-added Mo, the thickness of the high-frequency electrode 124 is preferably 0.05 mm or more. If the thickness of the high-frequency electrode 124 is less than 0.05 mm, it is difficult to manufacture the high-frequency electrode 124. In addition, the thickness of the high-frequency electrode 124 is not particularly limited as long as it is smaller than the thickness of the ceramic base material 110, but is preferably 10 mm or less, more preferably 5 mm or less, and even more preferably 2 mm or less. The amount of rare earth oxide is effective when it is 0.1wt% to 5wt%. In that case, the particle size is 5 to 15μm. When no rare earth oxide is added, the particle size is 30 to 100μm.
[0018] When the high-frequency electrode 124 is formed of a mesh woven from rare-earth-doped Mo wires, the wire diameter is preferably 0.03 mm or more and 0.05 mm or less.
[0019] As shown in the enlarged view of FIG. 3(a), the high-frequency electrode 124 has a plurality of through holes 128 formed therein so as to be distributed over the entire surface. The electrode may also be cut into a predetermined pattern. When the high-frequency electrode 124 is formed of a rare-earth-doped Mo foil or plate, the plurality of through holes 128 can be formed by hole processing (machine processing such as punching or laser processing). Alternatively, for example, a mask of a predetermined shape can be formed on the upper surface of the rare-earth-doped Mo foil using a photoresist or dry film, and the plurality of through holes 128 can be formed by etching using an etching solution containing a mixture of phosphoric acid, nitric acid, acetic acid, and water. The high-frequency electrode 124 can also be formed by, for example, a mesh woven from rare-earth-doped Mo wires. In this case, it is preferable to plain-weave the rare-earth-doped Mo wires, but other weaving methods such as twill weaving may also be used.
[0020] In the following description, the ratio of the total open area of the through holes 128 to the area of the top surface of the high-frequency electrode 124 when no through holes 128 are formed is referred to as the open area ratio. In the case of a mesh electrode, the open area ratio refers to the proportion of space in a certain area, and is expressed in mm as {opening size / (opening size+wire diameter)} 2 ×100(%). By adjusting the aperture ratio, the impedance of the high-frequency electrode 124 can be adjusted. In particular, when a plurality of through holes 128 are formed by etching, the shape and dimensions of the openings of the through holes 124 can be easily adjusted. For example, openings with different dimensions can be mixed. This makes it possible to easily adjust the aperture ratio and therefore the impedance of the high-frequency electrode 124. Note that the shape of the openings of the through holes 128 is not limited to a circle, but can be a polygon (for example, a hexagon, a square, or a triangle). In the case of a mesh, the wire diameter or pitch (opening size+wire diameter) can be adjusted.
[0021] Instead of the high-frequency electrode 124, or in addition to the high-frequency electrode 124, an electrostatic adsorption electrode 126 (see FIG. 3(b)) may be embedded inside the ceramic base material 110. The electrostatic adsorption electrode 126 is preferably embedded above the high-frequency electrode 124. The electrostatic adsorption electrode 126 has two semicircular electrodes 126a and 126b arranged to face each other at a predetermined interval, and has a substantially circular shape as a whole. For example, the outer diameter of the electrostatic adsorption electrode 126 can be set to 298 mm. The wafer 10 can be electrostatically adsorbed by applying a predetermined voltage (for example, ±500 V) to each of the electrodes 126a and 126b. The electrostatic adsorption force can be adjusted by adjusting the aperture ratio. The electrostatic adsorption electrode 126 has the same configuration as the high-frequency electrode 124 except for the shape, and therefore a detailed description thereof will be omitted. The heater electrode 122, the high frequency electrode 124, and the electrostatic attraction electrode 126 may share functions with one another and may be collectively referred to as electrodes 120.
[0022] As shown in FIG. 4, the heater electrode 122 is formed of a metal mesh or foil cut into a strip shape. The heater electrode 122 has an outer diameter of 298 mm. The heater electrode 120 is not exposed from the side of the ceramic base material 110. A terminal portion 122T to be connected to the power supply line 140 (see FIG. 1) is provided at approximately the center of the heater electrode 122. The heater electrode 122 is formed of a heat-resistant metal (high melting point metal) such as a mesh or foil woven with wires of tungsten (W), molybdenum (Mo), or an alloy containing molybdenum and / or tungsten. As with the high-frequency electrode 124, it can also be formed of rare earth-added Mo. The heater electrode 122 has a thickness of 0.15 mm or less. Here, the thickness refers to the value at the point excluding the intersection of the wires in the case of a mesh. From the viewpoint of increasing the resistance value of the heater electrode 122 and reducing the current consumption of the ceramic heater 100, it is preferable that the wire diameter is 0.1 mm or less and the thickness of the heater electrode 122 is 0.1 mm or less excluding the intersections of the wire. In particular, it is preferable that the wire diameter is 0.03 mm or more and 0.05 mm or less. Moreover, the width of the heater electrode 122 cut into a strip shape is preferably 2.5 mm to 20 mm, and more preferably 5 mm to 15 mm. In this embodiment, the heater electrode 122 is cut into the shape shown in FIG. 4, but the shape of the heater electrode 122 is not limited to this and can be changed as appropriate.
[0023] As shown in FIGS. 1 and 2, a shaft 130 is connected to a lower surface 113 of the ceramic base 110. The shaft 130 has a hollow, generally cylindrical cylindrical portion 131 and two large diameter portions 132 and 133. The large diameter portion 132 is provided above the cylindrical portion 131 (see FIG. 2), and the large diameter portion 133 is provided below the cylindrical portion 131 (see FIG. 1). The large diameter portions 132 and 133 have a diameter larger than that of the cylindrical portion 131. In the following description, the longitudinal direction of the cylindrical portion 131 is defined as the longitudinal direction 6 of the shaft 130. As shown in FIG. 1, in a state in which the ceramic susceptor 100 is in use, the longitudinal direction 6 of the shaft 130 is parallel to the up-down direction 5.
[0024] 2, a protrusion 114 for joining to a shaft 130 (hereinafter referred to as a joining protrusion 114) is provided on a lower surface 113 of the ceramic base material 110. There is no particular upper limit on the height of the joining protrusion 114, but in consideration of ease of manufacture, the height of the joining protrusion 114 is preferably 20 mm or less.
[0025] The upper surface of the cylindrical portion 131 is fixed to the lower surface 114B of the joining protrusion 114 of the ceramic base 110. The shaft 130 may be made of a ceramic sintered body such as aluminum nitride, silicon carbide, alumina, silicon nitride, or the like, like the ceramic base 110. Alternatively, in order to improve heat insulation, the shaft 130 may be made of a material having a lower thermal conductivity than the ceramic base 110.
[0026] As shown in FIG. 2, the shaft 130 has a hollow cylindrical shape, and a through hole extending in the longitudinal direction 6 (see FIG. 1) is formed inside (a region inside the inner diameter). A power feeder 140 for supplying power to the heater electrode 122 and a power feeder 141 for supplying power to the high-frequency electrode 124 are arranged in the hollow part (through hole) of the shaft 130. Note that in FIG. 2, only one each of the power feeders 140 and 141 is shown, but in reality, a plurality of power feeders 140 and a plurality of power feeders 141 are arranged. The upper end of the power feeder 140 is electrically connected to a terminal portion 122T (see FIG. 4) arranged in the center of the heater electrode 122. The power feeder 140 is connected to a heater power source (not shown). As a result, power is supplied to the heater electrode 122 via the power feeder 140. Similarly, power is supplied to the high-frequency electrode 124 via the power feeder 141.
[0027] 2, the second gas flow passage 168 extending in the up-down direction 5 is formed in the cylindrical portion 131 of the shaft 130. As described above, the upper end of the second gas flow passage 168 is connected to the lower end of the first gas flow passage 164. Note that in the above description, the shaft 130 is provided in the ceramic base 110. However, there may be cases in which the shaft 130 is not provided in the ceramic base 110 in the ceramic susceptor 100.
[0028] Next, a method for manufacturing the ceramic susceptor 100 will be described. In the following, a case where the ceramic base 110 and the shaft 130 are made of aluminum nitride will be described as an example. For the sake of simplicity, it is assumed that only the high-frequency electrode 124 is embedded in the ceramic base 110.
[0029] First, a method for manufacturing the ceramic base material 110 will be described. As shown in FIG. 5(a), granulated powder Q mainly composed of aluminum nitride (AlN) powder is put into a bed-type carbon mold 601 and pre-pressed with a punch 602. The granulated powder Q preferably contains 5 wt% or less of a sintering aid (for example, Y2O3). A rare earth-added Mo foil or plate having a thickness of 0.05 mm or more is prepared as the high-frequency electrode 124. Then, a plurality of through holes 128 are formed in the high-frequency electrode 124 by etching or the like. Alternatively, the high-frequency electrode 124 can be formed by a mesh woven with rare earth-added Mo wires having a predetermined opening ratio. Next, as shown in FIG. 5(b), the high-frequency electrode 124 cut into a predetermined shape is placed on the pre-pressed granulated powder Q. The high-frequency electrode 124 is placed so as to be parallel to a surface perpendicular to the pressure direction (the bottom surface of the bed-type mold 601). At this time, a W pellet or a Mo pellet may be embedded at the position of terminal 124T of high-frequency electrode 124 (see FIG. 3(a)).
[0030] As shown in FIG. 5(c), granulated powder Q is further poured into the bed-type mold 601 so as to cover the high-frequency electrode 124, and pressed and molded with a punch 602. At this time, the amount of granulated powder Q covering the high-frequency electrode 124 can be adjusted so that the high-frequency electrode 124 is embedded at a depth of 0.3 mm or more. Next, as shown in FIG. 5(d), the granulated powder Q in which the high-frequency electrode 124 is embedded is fired in a pressed state. The pressure applied during firing is preferably 1 MPa or more. In addition, firing is preferably performed at a temperature of 1800° C. or more. Note that firing can also be performed multiple times. Next, as shown in FIG. 5(e), in order to form the terminal 124T, a blind hole is machined up to the high-frequency electrode 124. Note that, if a pellet is embedded, a blind hole is machined up to the pellet. Furthermore, a through hole for forming the gas flow path 164 may be formed as necessary. This allows the ceramic base material 110 in which the gas flow path 164 is formed inside to be produced. Incidentally, the through-hole is insulated from the heater electrode 122, the high-frequency electrode 124, and the electrostatic attraction electrode 126 as necessary. Insulated means that the electrodes are not exposed in the through-hole, or an insulating sleeve is inserted in the through-hole, or the like.
[0031] The ceramic substrate 110 can also be manufactured by the following method. As shown in Fig. 6(a), a binder is added to aluminum nitride granulated powder Q, which is then CIP molded and processed into a disk shape to produce an aluminum nitride compact 610. Next, as shown in Fig. 5(b), the compact 610 is degreased to remove the binder.
[0032] As shown in FIG. 6(c), a recess 611 for embedding the high-frequency electrode 124 is formed in the degreased molded body 610. The recess 611 may be formed in advance in the molded body 610. As described above, a rare-earth-added Mo foil or plate having a thickness of 0.05 mm or more is prepared as the high-frequency electrode 124, and a plurality of through holes 128 are formed in the high-frequency electrode 124 by etching or punching. Alternatively, the high-frequency electrode 124 is formed by a mesh woven with rare-earth-added Mo wires having a predetermined aperture ratio. The high-frequency electrode 124 is placed in the recess 611 of the molded body 610, and another molded body 610 is laminated. At this time, the thickness of the other molded body 610 can be adjusted so that the high-frequency electrode 124 is embedded at a depth of 0.3 mm or more. Next, as shown in FIG. 6(d), the laminated molded bodies 610 sandwiching the high-frequency electrode 124 are fired in a pressed state to produce a fired body. The pressure applied during firing is preferably 1 MPa or more. It is also preferable to perform the firing at a temperature of 1800° C. or higher. The firing can be performed multiple times. The steps after the production of the fired body are the same as those described above, and therefore the explanation is omitted.
[0033] The upper surface 111 of the ceramic base 110 thus formed is ground and polished. This allows the distance in the vertical direction 5 from the upper surface 111 of the ceramic base 110 to the high-frequency electrode 124 to be adjusted. For example, the distance in the vertical direction 5 from the upper surface 111 of the ceramic base 110 to the high-frequency electrode 124 can be adjusted to be 0.3 mm or more. Furthermore, the upper surface 111 is sandblasted to form a plurality of convex portions 156 and annular convex portion 152 on the upper surface 111. Note that sandblasting is a suitable processing method for forming the plurality of convex portions 156 and annular convex portion 152, but other processing methods can also be used.
[0034] The shaft 130 is bonded and fixed to the approximate center of the lower surface 112 of the ceramic base 110 thus formed in an inert atmosphere at 1600° C. or higher to manufacture the ceramic susceptor 100. The shaft 130 is formed by forming granulated powder P of aluminum nitride to which several wt % of binder has been added under hydrostatic pressure (about 1 MPa), processing the formed body into a predetermined shape, and then firing it in a nitrogen atmosphere. EXAMPLES
[0035] The present invention will be further described below using Examples 1 to 9. However, the present invention is not limited to the Examples described below. In addition, Figs. 7 to 9 show tables showing the results of Examples 1 to 9. Fig. 10 shows a table showing the results of Comparative Examples 1 and 2.
[0036] [Example 1] The ceramic susceptor 100 (see FIG. 2) of Example 1 will be described. In Example 1, a ceramic base material 110 having a diameter of 310 mm and a thickness of 25 mm was produced by the above-mentioned production method using aluminum nitride (AlN) to which 5 wt% of a sintering aid (Y2O3) was added as a raw material. A high-frequency electrode 124 cut into a predetermined pattern was embedded at a position 1.0 mm below the upper surface 111 of the ceramic base material 110. In other words, the thickness D (see FIG. 2) of the ceramic insulating layer was 1.0 mm. The high-frequency electrode 124 was formed using a Mo plate material (thickness 0.1 mm, outermost diameter 298 mm) to which 3 wt% of La2O3 was added. A through hole 128 having a diameter of 6 mm was formed at each vertex position when a regular square with a side of 8 mm was laid out over the entire surface of the high-frequency electrode 124. The aperture ratio of the high-frequency electrode 124 was 44.2%. The through hole 128 was formed by punching processing. Furthermore, two terminals were provided for measuring the resistance value of the high-frequency electrode 124 .
[0037] In the ceramic susceptor 100 of Example 1, the resistance value of the high-frequency electrode 124 after firing (first heat treatment, 1850° C.) was 0.12Ω, and the resistance value of the high-frequency electrode 124 after shaft joining (second heat treatment, 1650° C.) and further after vacuum brazing (third heat treatment, 1000° C.) was 0.12Ω. The average particle size of Mo constituting the high-frequency electrode 124 was 12 μm.
[0038] An insulation test was performed on the ceramic susceptor 100 of Example 1 produced in the following manner. First, a silicon wafer was placed on the ceramic susceptor 100, and a voltage of DC 1 kV was applied between the high-frequency electrode 124 and the silicon wafer, and the insulation resistance was measured with an insulation resistance meter. A thermal cycle test was performed in which the ceramic susceptor 100 was heated to 200°C, then heated to 600°C, and then returned to 200°C for 20 cycles. Thereafter, the insulation resistance was measured again under the same conditions, and the change in insulation resistance before and after the thermal cycle test was measured. When the rate of change in insulation resistance was δ, the case where δ≦20% was evaluated as ◎, the case where 20%<δ≦35% was evaluated as ○, the case where 35%<δ≦50% was evaluated as △, and the case where δ>50% was evaluated as ×. In Example 1, the result of the insulation test was evaluated as ○.
[0039] [Example 2] The ceramic susceptor 100 of Example 2 is similar to the ceramic susceptor 100 of Example 1, except that the through holes 128 are formed by etching, not punching. When the ceramic susceptor 100 of Example 2 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0040] [Example 3] The ceramic susceptor 100 of Example 3 is similar to the ceramic susceptor 100 of Example 1, except that the through holes 128 are formed by etching instead of punching, and the high-frequency electrode 124 is embedded at a position 0.3 mm below the upper surface 111 of the ceramic base material 110, i.e., the thickness D (see FIG. 2) of the ceramic insulating layer is 0.3 mm. When the ceramic susceptor 100 of Example 3 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0041] [Example 4] The ceramic susceptor 100 of Example 4 is similar to the ceramic susceptor 100 of Example 1, except that the through holes 128 are formed by etching instead of punching, and the high-frequency electrode 124 is formed using a Mo plate material (thickness 0.1 mm) to which 3 wt % of CeO2 is added. When the ceramic susceptor 100 of Example 4 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0042] In the ceramic susceptor 100 of Example 4, the resistance value of the high-frequency electrode 124 after the first firing was 0.14Ω, and the resistance value of the high-frequency electrode 124 after the third firing was 0.13Ω.
[0043] [Example 5] The ceramic susceptor 100 of Example 5 is similar to the ceramic susceptor 100 of Example 1, except that the high-frequency electrode 124 (and the through-holes 128) are formed using a mesh (mesh size #50) made by plain weaving Mo wire (wire diameter 0.1 mm) to which 3 wt % of La2O3 has been added. The aperture ratio of the high-frequency electrode 124 was 64.6%. When the ceramic susceptor 100 of Example 5 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0044] [Example 6] The ceramic susceptor 100 of Example 6 is similar to the ceramic susceptor 100 of Example 1, except that the high-frequency electrode 124 (and the through-holes 128) are formed using a mesh (mesh size #200) made by plain weaving Mo wire (wire diameter 0.04 mm) to which 3 wt % of La2O3 has been added. The aperture ratio of the high-frequency electrode 124 was 46.9%. When the ceramic susceptor 100 of Example 6 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0045] [Example 7] The ceramic susceptor 100 of Example 7 is similar to the ceramic susceptor 100 of Example 5, except that in addition to the high-frequency electrode 124, a heater electrode 122 made of a mesh (mesh size #50) made of a plain-woven Mo wire (wire diameter 0.1 mm) to which no rare earth additives are added is embedded at a position 12 mm below the upper surface 111 of the ceramic base material 110. The heater electrode 122 was formed using a mesh (mesh size #50) made of a plain-woven Mo wire (wire diameter 0.1 mm). An insulation test was performed on the ceramic susceptor 100 of Example 7 in the same manner as in Example 1, and the result of the insulation test was evaluated as ⊚.
[0046] [Example 8] The ceramic susceptor 100 of Example 8 is similar to the ceramic susceptor 100 of Example 5, except that in addition to the high-frequency electrode 124, a heater electrode 122 made of a mesh (mesh size #50) of Mo wire (wire diameter 0.1 mm) with 3 wt % of La2O3 added thereto is embedded in a position 12 mm below the upper surface 111 of the ceramic base material 110, instead of a mesh (mesh size #50) of Mo wire (wire diameter 0.1 mm) with no additive. An insulation test was performed on the ceramic susceptor 100 of Example 8 in the same manner as in Example 1, and the result of the insulation test was evaluated as ⊚.
[0047] [Example 9] The ceramic susceptor 100 of Example 9 is similar to the ceramic susceptor 100 of Example 6, except that in addition to the high-frequency electrode 124, a heater electrode 122 made of a mesh (mesh size #200) made of a plain-woven Mo wire (wire diameter 0.04 mm) to which 3 wt % of La2O3 is added is embedded at a position 12 mm below the upper surface 111 of the ceramic base material 110, instead of the mesh (mesh size #50) made of a plain-woven Mo wire (wire diameter 0.1 mm) to which 3 wt % of La2O3 is added. When the ceramic susceptor 100 of Example 9 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as ⊚.
[0048] [Comparative Example 1] The ceramic susceptor of Comparative Example 1 is similar to the ceramic susceptor 100 of Example 1, except that the high-frequency electrode is formed using a Mo plate material (thickness 0.1 mm) to which no rare earth oxide is added. When the ceramic susceptor 100 of Comparative Example 1 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as fair.
[0049] In the ceramic susceptor of Comparative Example 1, the resistance value of the high-frequency electrode after the first firing was 0.28Ω, and the resistance value of the high-frequency electrode after the third firing was 0.24Ω. The average particle size of Mo constituting the high-frequency electrode was 33 μm.
[0050] [Comparative Example 2] The ceramic susceptor of Comparative Example 2 is similar to the ceramic susceptor 100 of Example 1, except that the high-frequency electrode is embedded at a position 0.2 mm below the upper surface 111 of the ceramic base 110, i.e., the thickness D (see FIG. 2) of the ceramic insulating layer is 0.2 mm. When the ceramic susceptor 100 of Comparative Example 2 was subjected to an insulation test similar to that of Example 1, the result of the insulation test was evaluated as fair.
[0051] <Effects of the embodiment> In the above embodiment, the ceramic susceptor 100 includes a ceramic base 110 and a metallic high-frequency electrode 124 and / or an electrostatic attraction electrode 126 embedded in the ceramic base 110. The high-frequency electrode 124 and / or the electrostatic attraction electrode 126 are embedded at a position 0.3 mm or more away from the upper surface 111 of the ceramic base 110 in the up-down direction 5. The high-frequency electrode 124 and / or the electrostatic attraction electrode 126 contain Mo as a main component and also contain a rare earth oxide. As described above, containing Mo as a main component means that the Mo content is 50% or more.
[0052] Comparing the above Example 1 and Comparative Example 1, it was found that when the high-frequency electrode 124 is made of a metal material containing Mo as a main component and having rare earth oxides added thereto, it is possible to further improve the insulating performance of the ceramic susceptor 100. Note that, when the electrostatic attraction electrode 126 is made of a metal material containing Mo as a main component and having rare earth oxides added thereto, the same technical effect can be achieved.
[0053] In addition, as can be seen by comparing Examples 1 and 4 with Comparative Example 1, when the high-frequency electrode 124 is made using Mo with rare earth oxides added, the resistance value of the high-frequency electrode 124 after co-firing with AlN ceramics can be reduced to about half compared to when Mo with no rare earth oxides added is used. This makes it possible to reduce the impedance inside the high-frequency electrode. Therefore, it is expected that the uniformity of the in-plane distribution of the plasma generated in the process using high frequency will be improved on the ceramic substrate 110 compared to the high-frequency electrode made using Mo with no rare earth oxides added.
[0054] Comparing Example 1 and Comparative Example 2, it was found that by embedding the high-frequency electrode 124 at a position 0.3 mm or more downward from the upper surface 111 of the ceramic base 110, that is, by setting the thickness D (see FIG. 2) of the ceramic insulating layer to 0.3 mm or more, it is possible to improve the insulating performance of the ceramic susceptor 100. Note that, even when the electrostatic attraction electrode 126 is embedded at a position 0.3 mm or more downward from the upper surface 111 of the ceramic base 110, a similar technical effect can be achieved.
[0055] As can be seen by comparing Example 1 and Comparative Example 1, when the high-frequency electrode 124 is made using Mo with rare earth oxides added, the particle size of Mo after co-firing with AlN ceramics can be made smaller than when Mo without rare earth oxides is used. In this case, grain boundary sliding occurs in Mo at high temperatures during co-firing, causing plastic deformation, and it is considered that the stress acting between the high-frequency electrode and the insulating layer of the AlN ceramics is relaxed. As a result, it is presumed that a ceramic susceptor 100 having an insulating layer with improved suppression of fluctuations in insulation resistance was made, even when the insulating layer is thin. The same technical effect can be achieved when the electrostatic attraction electrode 126 is made using Mo with rare earth oxides added.
[0056] In the above embodiment, the high-frequency electrode 124 and / or the electrostatic attraction electrode 126 can be formed of a foil or plate of rare-earth-added Mo. In this case, since the multiple through-holes 128 can be formed by machining (punching with a mold), laser processing, etching, or the like, the size, shape, and position of the opening of the through-hole 128 can be easily adjusted. In addition, the aperture ratio can also be easily adjusted. As a result, it becomes easy to adjust the chucking force characteristics (chucking force, residual chucking force) of the electrostatic chuck, particularly with respect to the electrostatic attraction electrode 126. In addition, when the high-frequency electrode 124 and / or the electrostatic attraction electrode 126 are formed of a mesh of rare-earth-added Mo, the aperture ratio can be adjusted by adjusting the wire diameter and mesh size. In addition, when the high-frequency electrode 124 and / or the electrostatic attraction electrode 126 are cut into a predetermined shape by laser processing or the like, the mesh M is frayed at the end, causing the wire to protrude (see FIG. 11). By forming the high-frequency electrode 124 and / or the electrostatic attraction electrode 126 from a foil or plate of rare-earth-doped Mo, it is possible to suppress poor insulation and poor voltage resistance caused by protruding wires.
[0057] When the multiple through holes 128 of the high-frequency electrode 124 are formed by machining such as punching, burrs protruding above the upper surface of the high-frequency electrode 124 remain at the openings of the through holes 128 (see FIG. 12(a)). In this case, the burrs are likely to cause variations in insulation resistance. In contrast, when the multiple through holes 128 of the high-frequency electrode 124 are formed by etching, burrs protruding above the upper surface of the high-frequency electrode 124 do not remain at the openings of the through holes 128 (see FIG. 12(b)). In other words, the outer edge parts of the openings of the multiple through holes 128 on the upper surface of the high-frequency electrode 124 do not protrude above the part of the upper surface of the high-frequency electrode 124 excluding the outer edge parts of the openings of the multiple through holes 128. This makes it possible to suppress variations in insulation resistance caused by burrs. In addition, the R dimension of the outer edge parts of the openings of the through holes 128 can be set to 0.5 mm or more in a cross-sectional view on a plane parallel to the up-down direction. This also contributes to suppressing variations in insulation resistance. The same technical effect can be achieved even when the plurality of through holes 128 of the electrostatic attraction electrode 126 are formed by etching.
[0058] In the above embodiment, the high-frequency electrode 124 can be formed of a mesh woven from rare-earth-doped Mo wires. When the high-frequency electrode 124 is formed from a mesh material, the stress caused by the difference in shrinkage rate and the difference in CTE between the AlN ceramics and the high-frequency electrode 124 during manufacturing can be alleviated by the flexibly deforming mesh woven from the wires. In this case, it is preferable that the wire diameter is small, for example, 0.03 mm or more and 0.05 mm or less. The same technical effect can be achieved when the electrostatic attraction electrode 126 is formed from a mesh woven from rare-earth-doped Mo wires.
[0059] The ceramic susceptor 100 of this embodiment can include a heater electrode 122 embedded in the ceramic base 110. This allows the ceramic susceptor 100 to be given a heating function.
[0060] The heater electrode 120 can be formed of a metal material containing Mo as a main component and containing rare earth oxides. In this case, as described above, the particle size of Mo can be made smaller after co-firing with the AlN ceramics, compared to the case where Mo is used without the addition of rare earth oxides. As a result, grain boundary sliding occurs in Mo at the high temperature during co-firing, causing plastic deformation, and the stress acting between the heater electrode 122 and the insulating layer of the AlN ceramics is alleviated.
[0061] The heater electrode 122 can be formed of a Mo mesh made by weaving Mo wires containing Mo as a main component. The wire diameter of the Mo wires can be 0.03 mm or more and 0.05 mm or less. The sheet resistance of the mesh can be increased by reducing the wire diameter of the heater electrode 120. This makes it easier to adjust the resistance value required for the heater electrode 122.
[0062] <Modification form> The above-described embodiment is merely an example and may be modified as appropriate. For example, the shapes, sizes, and thicknesses of the heater electrode 122, the high-frequency electrode 124, and the electrostatic attraction electrode 126 are not limited to those in the above-described embodiment and may be modified as appropriate.
[0063] The shape, thickness, etc. of the ceramic base 110 may be changed as appropriate. The dimensions of the annular protrusion 152, such as the height and width, and the shape of the upper surface 152a of the annular protrusion 152 may be changed as appropriate. The height and shape of the upper surface 156a of the multiple protrusions 156 may be changed as appropriate. For example, the shape of the upper surface 156a of the multiple protrusions 156 does not necessarily have to be circular, and can be an appropriate shape, such as a square.
[0064] Although the present invention has been described above using the embodiment and its modified form, the technical scope of the present invention is not limited to the above description. It is obvious to those skilled in the art that various modifications or improvements can be made to the above embodiment. It is also clear from the claims that such modifications or improvements can be included in the technical scope of the present invention.
[0065] The order of execution of each process in the manufacturing method shown in the specification and drawings is not particularly specified, and may be any order unless the output of a previous process is used in a subsequent process. For convenience, even if the description uses "first," "next," etc., it does not mean that the process must be performed in that order. [Explanation of symbols]
[0066] 100 Ceramic susceptor 110 Ceramic substrate 122 Heater electrode 124 High Frequency Electrodes 126 Electrostatic Adsorption Electrode 130 Shaft 140 Feed line
Claims
1. A ceramic substrate having an upper surface and a lower surface facing the upper surface in a vertical direction; A metal electrode is embedded at a position 0.3 mm or more away from the upper surface of the ceramic base in the vertical direction, The electrode is a ceramic susceptor containing Mo as a main component and also containing a rare earth oxide.
2. 2. The ceramic susceptor according to claim 1, wherein the electrode is formed of a Mo foil or Mo plate containing Mo as a main component, and the Mo foil or Mo plate has a plurality of through holes penetrating the Mo foil or Mo plate in the vertical direction.
3. 3. The ceramic susceptor according to claim 2, wherein the outer edge portions of the openings of the plurality of through holes in the upper surface of the electrode do not protrude above the portions of the upper surface of the electrode excluding the outer edge portions of the openings of the plurality of through holes.
4. 2. The ceramic susceptor according to claim 1, wherein the electrodes are formed of Mo meshes made by plain weaving Mo wires containing Mo as a main component.
5. 5. The ceramic susceptor according to claim 4, wherein the Mo wire has a wire diameter of 0.03 mm or more and 0.05 mm or less.
6. 6. The ceramic susceptor according to claim 2, further comprising a heater electrode embedded in the ceramic base.
7. 7. The ceramic susceptor according to claim 6, wherein the heater electrode contains Mo as a main component and also contains a rare earth oxide.
8. 8. The ceramic susceptor according to claim 7, wherein the heater electrode is formed of a Mo mesh woven from Mo wires containing Mo as a main component, and the wire diameter of the Mo wires is 0.03 mm or more and 0.05 mm or less.
9. Preparing an electrode containing Mo as a main component and containing a rare earth oxide; Embedding the electrode in a ceramic granulated powder or a ceramic molded body; sintering the ceramic granulated powder or the ceramic molded body having the electrodes embedded therein to form a ceramic substrate; adjusting a position where the electrode is embedded in the ceramic granulated powder or the ceramic molded body, or processing the upper surface of the ceramic base so that a distance between the upper surface of the ceramic base and an upper surface of the electrode is 0.3 mm or more.
Citation Information
Patent Citations
Electrostatic chuck
JP2003077995A